Renewing and improving the business model toward sustainability in theory and practice - Mara Del Baldo; Maria Gabriella Baldarelli (International Journal of Corporate Social Responsibility (JCSR), 2017)
The paper aims to analyse and discuss the evolution towards a sustainable business model and to focus on the motivations and the implications on the mission, the governance and the accountability of companies. Moreover, the theoretical framework of values-based, ethical and sustainable leadership has been used as interpretative key for the case-study analysis. After presenting the literature review, the second part of the work is based on the inductive approach applied to the analysis of the experience of an Italian medium-sized company (SGR Group) belonging to the energy sector (oil & gas). Recently this company has started a new project aimed at renewing its business model and deepening its sustainability orientation, which has already been experienced for years. The project is finalized at identifying and assessing vices and virtues which affect the governance and the leadership model, as well as the company's stakeholders engagement processes. The case exemplifies a resilience capability derived from a sustainable business model activated through relationships among internal and external stakeholders and supported by an ethical-based transformational leadership model which, in turn, derives from and nurtures the coherence among the mission-governance and accountability model. Specifically, the analysis confirms the propositions drawn from the literature review relative to the fact that the coherence among mission, governance and accountability is a key driver for effective business model and that sustainable business models derive from and are characterized by sustainable leadership models, which include transformational, ethical-based and values-virtues-driven leadership.
Keywords: 650; Business model; Sustainability; Sustainable business model; Sustainable leadership; Values-based leadership; Mission; Governance; Accountability